1988
DOI: 10.1021/ma00181a045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of rodlike macromolecules in nondilute solutions: poly(n-alkyl isocyanates)

Abstract: Theories of caging of rigid rodlike molecules of length L and diameter d in semidilute solution are extended to higher concentrations. Packing considerations indicate that ordering in concentrated rigid rod systems must occur below CL2d = 2.26, where C is the number concentration of rods. In addition, the concentration at which the mean square deflection of a semiflexible polymer chain is equal to the cage size is calculated in terms of the ratio of the persistence length to the contour length. These and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…Nonrandom orientation of fibrils may occur simply due to hard core interactions at high concentrations. Keep and Pecora (1988) showed that a nonrandom orientation of rods must occur at NL2d > 2.26, and may occur at lower values. If fibril length and/or fibril density is greater at the higher ionic strength, then hard-core interactions alone could account for the difference in fibril orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonrandom orientation of fibrils may occur simply due to hard core interactions at high concentrations. Keep and Pecora (1988) showed that a nonrandom orientation of rods must occur at NL2d > 2.26, and may occur at lower values. If fibril length and/or fibril density is greater at the higher ionic strength, then hard-core interactions alone could account for the difference in fibril orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanations for the anomalously low diffusivities are the formation of loose fibril aggregates and the onset of caging, in which the rotational and sideways translational diffusion are reduced due to the effect of interactions with neighboring rods. The effect of caging is estimated to become measurable at values of NL3 > 35-50 (Keep and Pecora, 1988), where N is the number density of rods. For fibrils with lengths of -1000 nm, and molecular weights of -107, the corresponding concentration of fibrils at which caging might be observed is -0.5-0.8 mg/ml, compared to influence dynamic properties such as diffusion without altering static properties such as radius of gyration.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The results from the relevant studies are not fully conclusive concerning three aspects: (i) the mechanisms for relaxing concentration fluctuations in solution, especially in the concentrated region, where a coupling of translational to rotational diffusion is expected; (ii) the reorientational relaxation dynamics; (iii) the dependence of the self-diffusion on molecular parameters and concentration. On the other hand, investigations of the orientational dynamics, which are of primary interest in such anisotropic molecules were conducted more by electric birefringence and less by PCS experiments, 7,11,[13][14][15] due to the small optical anisotropy of these systems, resulting in difficult, and sometimes ambiguous, measurements. Recent advances in macromolecular chemistry have led to the synthesis of well-defined poly(p-phenylenes), PPP, with aliphatic side chains, with varying molecular weights and much higher optical anisotropies compared to other molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Additional insight into each mode is gained by decoupling the slow mode from the fast mode. ∆n′ 2 ) ∆n′ f 2 + ∆n′ s 2 + 2∆n′ f ∆n′ s cos[2( ′ s -′ f )] (12) tan(2 ′) ) ∆n′ s sin(2 ′ s ) + ∆n′ f sin(2 ′ f ) ∆n′ s cos(2 ′ s ) + ∆n′ f cos(2 ′ f ) (13) Shear rate, γ , dependence of the steady state dichroism orientation angle, ′′.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional studies have been limited to the two extremes of flexibility: the fully flexible chain and the rigid rod. [11][12][13][14][15] A previous rheo-optical study of linear PHIC has shown that concentration scaling of the shear response of the refractive index tensor, n xy is dependent on the chain flexibility. [1][2][3][4][5] However, there are a great many systems that fall between these two stiffness regimes.…”
Section: Introductionmentioning
confidence: 99%